1988
DOI: 10.1148/radiology.168.1.3380964
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral assessment: new dual-energy CT approach.

Abstract: Most clinical quantitative computed tomographic (CT) determinations of bone mineral content are hampered by inability to properly account for the various substances contained within the spongiosa (spongy bone). In general, the presence of adipose tissue lowers the CT numbers (Hounsfield units) and leads to underestimation of bone mineral content. Collagen matrix has the opposite effect. A new approach to obtaining data from postreconstruction dual-energy CT scans accounts for five principal constituents of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…It is possible to reduce this 5-fold (66,69). A high kilovoltage also is undesirable because it increases the large accuracy errors (at least 15-25%) associated with variable marrow fat and varying osteoid (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98). Gluer et al (99) showed an error of ash density of 8 mg/cm3 for every 100 mg/cm3 change of marrow fat, but the error at higher energies is 10-13 mg/cm3, i.e., 30-50% greater (85,92,(99)(100)(101).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…It is possible to reduce this 5-fold (66,69). A high kilovoltage also is undesirable because it increases the large accuracy errors (at least 15-25%) associated with variable marrow fat and varying osteoid (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98). Gluer et al (99) showed an error of ash density of 8 mg/cm3 for every 100 mg/cm3 change of marrow fat, but the error at higher energies is 10-13 mg/cm3, i.e., 30-50% greater (85,92,(99)(100)(101).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Initial studies involving early dual-energy CT concepts for BMD evaluation were published more than 2 decades ago (14,15). Recently, a novel approach for regional BMD assessment with dual-energy CT has been presented (16).…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
“…Image analysis was based on a threematerial decomposition algorithm for the bone mineral, yellow marrow and red marrow. [18][19][20][21] For our evaluation of the vertebral bodies, the relative contrast material ratio was set to a value of 1.75, and the range of the filter was set to 3 based on the experience from previous studies. 5,11,22,23 Non-calcium images were displayed in greyscale.…”
Section: Dual-source Ct Protocolmentioning
confidence: 99%